Unformatted text preview: x = c ( t − t ) and u (0 , t ) = g ( t ) = g t − x c 42 2 4 6 821 1 2 3 4 x t x  ct > 0 x  ct < 0 xct=0 u(x,0)=f(x) u(0,t)=g(t) Figure 48: Domain and characteristics for problem 3b The solution is therefore given by u ( x, t ) = f ( x − ct ) f o r x − ct > g t − x c for x − ct < 250...
View
Full
Document
This note was uploaded on 12/22/2011 for the course MAP 2302 taught by Professor Bell,d during the Fall '08 term at UNF.
 Fall '08
 BELL,D

Click to edit the document details